Photoelectron momentum distribution of hydrogen atoms in a superintense ultrashort high-frequency pulse - Wang, Jun; Li, Gen-Liang; Liu, Xiaoyu; Zhu, Feng-Zheng; Jiao, Li-Guang; Liu, Aihua (Frontiers in Physics, 2022)
By numerically solving the time-dependent Schrodinger equation, the photo-electron momentum distribution of ground state hydrogen atoms in the presence of super-intense ultra-short high-frequency pulses is examined. The photo-electron momentum distribution by a circularly polarized field in a weak laser field is the superposition of two perpendicular linearly polarized fields. The photoelectron momentum distribution can be drastically modified by the dynamic interference effect within a super-intense XUV laser field. In this paper, we show that when hydrogen atoms are exposed to a super-intense circularly polarized laser pulse with photon energy ω=53.605 eV, an obvious dynamic interference pattern occurs, which has previously been observed for linearly polarized pulses or the weakly bounded model H^- system for circularly polarized pulses. For the linear super-intense XUV pulses with equivalent intensity, the angular-distorted interference pattern occurs. The Coulomb re-scattering effect is responsible for the observed substantial variations in photoelectron momentum distributions by linearly and circularly polarized XUV pulses.